THE INFLUENCE OF BRAND AUTHENTICITY, BRAND SELF-CONGRUENCE, AND BRAND LOVE TOWARDS BRAND ENGAGEMENT OF TOURIST DESTINATION IN WEST SUMATERA (Economic Education Faculty of Economics and Business Universitas PGRI Sumatera Barat, 2022)
This study aims to analyse the effect of brand authentic, brand self-congruence, and brand love on brand engagement of tourist destinations in West Sumatra. The research population is all tourists who have visited West Sumatra tourist destinations in the last 5 years. The sample was collected using a simple random sampling technique and the questionnaire distributed to 585 respondents. The data analysis technique used is multiple regression analysis. The results showed that (1) brand authenticity had a positive and significant effect on destination brand engagement. (2) brand self-congruence has a positive and significant effect on destination brand engagement, (3) brand love has a positive and significant effect on destination brand engagement.